MORPHOLOGICAL AND IMMUNOHISTOCHEMICAL FEATURES OF THE ENDOMETRIUM IN THE FIRST TRIMESTER IN WOMEN WITH NORMAL PREGNANCY - Ixtiyorova, Gulchehra; Matrizaeva, Gulnora (International Journal of Scientific Pediatrics, 2023)
Abstract. Pathomorphological characteristics of gravid endometrium in normal infertility in the first trimester of pregnancy, differentiation and transformation into fibroblast-like cells and predecidual cells differed from the cells in uncomplicated pregnancy by their cytological diversity and polymorphic appearance. The purpose of the research: to study the clinical-morphological and immunohistochemical characteristics of the decidual layer of the endometrium of the uterus and to create an algorithm for identifying pathological changes in the inability to carry a normal fetus in the first trimester of pregnancy. Research materials and methods: in RIO and RIATM Khorezm Branch and Perinatal Center of Khorezm Region during the period of 2021-2023, the extract from the uterus of women who underwent curettage and aspiration of the uterine cavity during the first trimester of pregnancy was examined. Sections were taken on the same day from the tissue obtained by uterine curettage or aspiration. The materials were processed according to the instructions for 16 hours in a Thermo Fisher Scientific histoprocessor, unification of methods of histological examination of biopsy and operative materials. Results: According to the immunohistochemical study, Ki 67 protein and SD34 expression were higher in the control group compared to the main group. This is due to the slowness of the proliferative processes in the decidual shell and the low adhesion of the vessels. Conclusion: the identified changes require further study of the problem by pathomorphologists, obstetrician-gynecologists, and immunologists to determine the pathomorphological mechanisms of the development of infertility in women. Immunohistochemistry allows more accurate diagnosis and control of the effectiveness of hormone therapy, provides an individual approach to the patient, and therefore allows optimization of hormone therapy schemes.